Development of a Web-Based Motorcycle Rental Application with Real-Time Status and Digital Financial Recording: information system; motorcycle rental; Supabase; Vercel; MSME - Sakina Sudin; Anggiah Salim; Nurafni Muhammad; Fitriani Duwila; Frenti Polulu (Ambidextrous Journal of Innovation Efficiency and Technology in Organization, 2026)
Motorcycle rental businesses at the Micro, Small, and Medium Enterprises (MSME) level are still largely managed manually, which may lead to transaction recording errors and delays in vehicle status information. This study aims to design and implement a web-based motorcycle rental information system developed using HTML, CSS, JavaScript, and Bootstrap as the user interface. The system is managed through a GitHub repository, utilizes Supabase as a real-time database, and is deployed on the Vercel platform to provide public domain access. The research method follows system development stages consisting of requirement analysis, system design, implementation, and testing. The system is able to display real-time motorcycle availability, support admin-managed rental transactions, and generate daily income reports. To protect the confidentiality of MSME financial data, the income report is limited to a three-day period. The results indicate that the system operates properly and is feasible to be used as an operational support tool for web-based motorcycle rental services.